Obras que ferem : a arte macabra de Ed Gein = Artworks that injure the flesh: the macabre art of Ed Gein - Maldonado, Stephanie Ares, 1992- (2020)
Orientadores: Eduardo José Marandola Junior, Gustavo Silvano Batista